Dielectric behaviour of Zn/Al-NO3 LDHs filled with polyvinyl chloride composite at low microwave frequencies - Salih, Ethar Y.; Abbas, Zulkifly; Al Ali, Samer Hasan Hussein; Hussein, Mohd Zobir (Hindawi Publishing Corporation, 2014)
Recently, researchers have shown great interest in improving the thermal, mechanical, dielectric, and microwave properties of pure polymers through the use of polymer-based composites. The essential properties of polymer-based composites can be modified by varying the amount of Zn/Al-NO3 layered double hydroxide (LDH) added to polyvinyl chloride (PVC). Therefore, by determining the optimal ratio of LDH in the PVC matrix, the dielectric properties of PVC-LDH composites can be improved. An LDH was prepared using the coprecipitation method, while PVC-LDH composites were prepared using tetrahydrofuran (THF) as the solvent. The composites were characterised using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM), and room temperature dielectric measurements were investigated using an RF Impedance/Material Analyzer (Agilent 4291). The results confirmed that the prepared composites were pure. Additionally, the presence of LDH in the PVC matrix was verified. The dielectric measurements showed that an increase in the LDH concentration leads to an increase in the dielectric constant and the dielectric loss factor. When used as dielectric filler in the PVC matrix, the LDH improved the dielectric properties of the fabricated composites. The results indicate that these composites show great potential for use as microwave absorbers at low microwave frequencies.